Trade Credit Financing Under Competition and Its Impact on Firm Performance in Supply Chains - Lee, Hsiao-Hui; Zhou, Jianer; Wang, Jingqi (Manufacturing and Service Operations Management, 2018)
Using a dyadic panel data set that links U.S. suppliers with their major buyers, we study how trade credit responds to various types of competition in supply chains, as well as the impact of trade credit on firm performance. We find that suppliers with smaller market share are associated with more trade credit, confirming that suppliers with weak market power use trade credit as a competitive tool. Next, we find that buyers with larger market share are associated with more trade credit, whereas suppliers selling to a concentrated buyer base are associated with less trade credit; by differentiating competition in buyers’ markets from competition between supply chain partners, we show that the two types of competition have different impacts on trade credit. In studying the impact of trade credit on firm performance, we make the distinction between an industry-average trade credit and an individual supply chain’s deviation from such an industry average. When suppliers offer trade credit at their industry-average level, this action facilitates trade and, thus, is positively associated with both parties’ performance; conversely, when suppliers are more aggressive in their trade credit strategy than the industry average, then the excess trade credit is negatively associated with buyer performance. One managerial message from our research is that buyers should be cautious about trade credit far exceeding the industry-average level. The online appendix is available at https://doi.org/10.1287/msom.2017.0640 . This paper has been accepted for the Manufacturing & Service Operations Management Special Issue on Interface of Finance, Operations, and Risk Management.